Synthesis, Antitubercular and Anticancer Activities of p-nitrophenylethylenediamine- Derived Schiff Bases - S. Amim, Raquel; Pessoa, Claudia; C. S. Lourenco, Maria; V. N. de Souza, Marcus; A. Lessa, Josane (Medicinal Chemistry, 2017)
Background: Schiff bases have been greatly studied in biological field due to their wide range of pharmacological activities, such as antitubercular and antitumour. In the search of novel antitubercular agents, several compounds containing pharmacophoric group of ethambutol have been synthesized and evaluated against mycobacteria species causing tuberculosis. In this work, we investigate whether ethylenediamine, Schiff base as well as nitro group together could contribute to the formation of novel molecules with dual biological activities: antitubercular and anticancer. Methods: A series of Schiff bases (3-12) derived from p-nitrophenylethylenediamine (1) as well as N1,N2-bis(4-nitrophenyl)ethane-1,2-diamine (2) were synthetized and assayed for their action against Mycobacterium tuberculosis H37Rv strain and the human tumour cell lines SF-295 (glioblastoma multiforme), HCT-116 (colon adenocarcinoma) and OVCAR-8 (ovarian cancer). Results: Among the compounds that showed antimycobacterial effects, 4 was more active than ethambutol, the antitubercular drug used as positive control. Also, compounds 1, 8, 10 and 12 were able to reduce strongly the viability of the tumour cell lines at 5 μgmL-1. Conclusion: According to studies, some modifications on p-nitrophenylethylenediamine (1) were an effective strategy to obtain compounds with antiproliferactive activities. Also, Schiff base 4 proved to be the lead antitubercular compound.
Keywords: cancer